2016
DOI: 10.3923/pjbs.2016.95.105
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pesticide Residues in Human Blood and Effects of Occupational Exposure on Hematological and Hormonal Qualities

Abstract: Pesticides are the first choice by farmers for use against plant pathogens, nevertheless their adverse effects to the environment. Current study was designed to measure pesticides residues in blood of spray farmers and to assess their possible effects. Blood indices and thyroid and reproductive hormones were evaluated in blood of adult male volunteers (20-48 years old). Volunteers were divided to three groups; spray-workers (directly-exposed), farmers who live in the country area (indirectly-exposed) and city … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Efek utama keracunan pestisida adalah gangguan sistem saraf seperti sakit kepala, pusing, paresthesia, tremor, diskoordinasi, kejang; serta menghambat enzim asetylcholinesterase yang menggangu organ gerak. Dampak jangka panjang pestisida antara lain anemia, anoreksia, berkurangnya berat badan dan gangguan fungsi hati (Agustina & Norfai, 2018;Arwin & Suyud, 2016;Azmi, Naqvi, Azmi, & Aslam, 2006;Britt & Budinky A, 2000;Fauziyyah, Suhartono, & Astorina, 2017;Kartini et al, 2019;Nassar, Salim, & Malhat, 2016;Neghab, Jalilian, Taheri, Tatar, & Haji Zadeh, 2018;Okvitasari, Anwar, & Suparmin, 2016;Patil, Patil, & Govindwar, 2003;Prasetyaningsih, Arisandi, & Retnosetiawati, 2017;Sihana, Dawson, & Buckley, 2019).…”
Section: Penggunaanunclassified
“…Efek utama keracunan pestisida adalah gangguan sistem saraf seperti sakit kepala, pusing, paresthesia, tremor, diskoordinasi, kejang; serta menghambat enzim asetylcholinesterase yang menggangu organ gerak. Dampak jangka panjang pestisida antara lain anemia, anoreksia, berkurangnya berat badan dan gangguan fungsi hati (Agustina & Norfai, 2018;Arwin & Suyud, 2016;Azmi, Naqvi, Azmi, & Aslam, 2006;Britt & Budinky A, 2000;Fauziyyah, Suhartono, & Astorina, 2017;Kartini et al, 2019;Nassar, Salim, & Malhat, 2016;Neghab, Jalilian, Taheri, Tatar, & Haji Zadeh, 2018;Okvitasari, Anwar, & Suparmin, 2016;Patil, Patil, & Govindwar, 2003;Prasetyaningsih, Arisandi, & Retnosetiawati, 2017;Sihana, Dawson, & Buckley, 2019).…”
Section: Penggunaanunclassified
“…Although the mechanisms by which aircraft engine oils significantly altered the levels of white blood cells, neutrophils, lymphocytes, eosinophils, eosinophil % and monocyte % in Sprague Dawley rats are not yet known, it is worthy to suggest that organophosphate components of these oils may have been a key player in the alteration process. This assertion is supported by various studies which reported adverse changes in blood indices for farm workers occupationally exposed to organophosphate pesticides ( Al-Sarar et al, 2009 ; Andreadis et al, 2013 ; Fareed et al, 2013 ; Nassar et al, 2016 ) . Hematocrit is another blood parameter that was affected by engine oil exposure.…”
Section: Discussionmentioning
confidence: 69%
“…An increased mean platelet volume is an indicator of larger and more reactive platelets resulting from an elevated turnover ( Martin et al, 1983 ) which represents a risk factor for overall vascular mortality ( Slavka et al, 2011 ) . Some studies have reported a decrease in mean platelet volume levels for farm workers exposed to pesticides ( Nassar et al, 2016 ; Varol et al, 2014 ) . Although it is may be worthy to insinuate that male rats resisted the G4-N-induced biochemical events that led to alteration of mean platelet volume levels in females, the mechanisms at play remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Limits of quantification (LOQ) were calculated from signal-to-noise ratios 1:10, which were obtained from the measurement of the samples with the lowest concentration level where peaks of studied pesticides were detected. 38 …”
Section: Methodsmentioning
confidence: 99%